2010
DOI: 10.1111/j.1365-2141.2010.08471.x
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and bone marrow engraftment of AML blasts is dependent on β‐catenin signalling

Abstract: SummaryB-catenin is the central effector molecule of the canonical Wnt signalling pathway, which controls self-renewal of haematopoietic stem cells. Deregulation of this pathway occurs in various malignancies including myeloid leukaemias. The present study examined the functional outcome of stable b-catenin down-regulation through lentivirus-mediated expression of short hairpin RNA (shRNA). Reduction of the b-catenin levels in acute myeloid leukaemia (AML) cell lines and patient samples decelerated their in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…It has been reported that β-catenin is expressed and activated in LSCs and that it is required for self-renewal (37,38). Thus, we postulated that SPARC expression may be higher in less differentiated hematopoietic cell subpopulations.…”
Section: Sparc Overexpression Ismentioning
confidence: 80%
See 1 more Smart Citation
“…It has been reported that β-catenin is expressed and activated in LSCs and that it is required for self-renewal (37,38). Thus, we postulated that SPARC expression may be higher in less differentiated hematopoietic cell subpopulations.…”
Section: Sparc Overexpression Ismentioning
confidence: 80%
“…Thus, the net result of the SPARC/integrin/ILK interplay is enhanced β-catenin. The latter is required for self-renewal of leukemia stem cells (LSCs) (37)(38)(39)(40)(41). Thus, we hypothesized that SPARC overexpression leads to aberrant β-catenin activation in AML.…”
Section: Sparc Overexpression Ismentioning
confidence: 99%
“…Certain studies have suggested that HIF-1α activation regulates the Wnt/β-catenin signaling pathway, which activates the expression of target genes and contributes to the enhanced invasion of hypoxic gastric cancer cells (35)(36)(37). CD44 is a target gene of the Wnt/β-catenin signaling pathway (38); therefore, the mechanism by which HIF-1α regulates CD44 may be associated with the Wnt/β-catenin signaling pathway in gastric cancer. Further studies are required to investigate these underlying mechanisms in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 To test whether inhibiting WNT signaling affected survival or differentiation of primary AML blasts with different levels of nuclear β-catenin, we used a compound (iCRT3) that inhibits WNT signaling by blocking the interaction between β-catenin and TCF family transcription factors.…”
Section: Letters To the Editormentioning
confidence: 99%